2022
DOI: 10.1097/pq9.0000000000000541
|View full text |Cite
|
Sign up to set email alerts
|

A Standardized Diagnostic Pathway for Suspected Appendicitis in Children Reduces Unnecessary Imaging

Abstract: Introduction: Ultrasound (US) for the diagnosis of acute appendicitis is often nondiagnostic, and additional imaging is required. A standardized approach may reduce unnecessary imaging. Methods: We retrospectively analyzed all patients who had imaging for appendicitis in our emergency department in 2017 and evaluated patient characteristics associated with nondiagnostic US. Using these results, we developed a pediatric appendicitis score (PAS)-based imaging pathway and compared imaging trends prepathway and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…However, this comes at an increased cost, with a 22% longer ED stay than reported in this study. 10 Previous studies with similar appendicitis rates and CT utilization to this study reported higher hospitalization rates, 51% 2 compared with 36% in this study, highlighting the admission reduction achieved when offering a next-day surgery clinic follow-up option. Hospital admission is sometimes necessary but costly and inconvenient solution to diagnostic uncertainty.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…However, this comes at an increased cost, with a 22% longer ED stay than reported in this study. 10 Previous studies with similar appendicitis rates and CT utilization to this study reported higher hospitalization rates, 51% 2 compared with 36% in this study, highlighting the admission reduction achieved when offering a next-day surgery clinic follow-up option. Hospital admission is sometimes necessary but costly and inconvenient solution to diagnostic uncertainty.…”
Section: Discussionsupporting
confidence: 67%
“…7 Others have described using a limited right lower quadrant MRI to reduce ionizing radiation exposure. 8,9 However, these gains in reduction of CT use resulted in increased utilization of MRI, longer ED length of stay (over 5 hours), 10 increased in-ED surgical consultation (70%), 11 and high rates of admission (above 50%). 2 These authors and others 13 have recommended follow-up for undifferentiated abdominal pain, yet none with pediatric surgeons.…”
Section: Problem Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…A combination of PAS and selective ultrasound (USS) has been observed to decrease rates of NA 1 . Unnecessary imaging in cases of low suspicion of appendicitis increases healthcare costs for minimal benefit 17 …”
Section: Introductionmentioning
confidence: 99%
“…1 Unnecessary imaging in cases of low suspicion of appendicitis increases healthcare costs for minimal benefit. 17 Several studies have demonstrated higher NA rates in nonpaediatric compared to paediatric surgical services. 18,19 This is particularly relevant as appendicectomy is the most common surgical operation performed by general surgeons on children.…”
Section: Introductionmentioning
confidence: 99%